Institutional Explanations for the Persistence of Poverty on First Nations Reserves in Canada: A Review of the Native American Economic Development Literature - Kelly, Liam D. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2023)
The institutions governing First Nations reserves in Canada are commonly cited as a key barrier to economic development. Despite these claims, few studies have empirically assessed the institutional arrangements governing reserves. Conversely, there is a much larger and more developed literature on Native American economic development and the institutions governing reservations. While there are many important differences between First Nations reserves and Native American reservations, there are several key similarities that allow for comparisons. First, the institutional arrangements governing land, specifically federal trusteeship over land, are broadly similar in both contexts. The restrictions on property, especially the prohibition on using reserve and reservation lands as collateral, also create important similarities in the availability of credit, mortgages, and other banking services. Finally, while Native American tribes generally have more sovereignty over their lands and economies, First Nations are increasingly reclaiming the right to manage their lands and economies with similar levels of autonomy. This review summarizes the Native American economic development literature in these three areas and identifies relevant considerations for First Nations in Canada. The article concludes with a discussion of future research priorities.